2011
DOI: 10.3389/fimmu.2011.00063
|View full text |Cite
|
Sign up to set email alerts
|

Marginal Zone B-Cells, a Gatekeeper of Innate Immunity

Abstract: To maintain the integrity of an organism constantly challenged by pathogens, the immune system is endowed with a variety of cell types. B lymphocytes were initially thought to only play a role in the adaptive branch of immunity. However, a number of converging observations revealed that two B-cell subsets, marginal zone (MZ) and B1 cells, exhibit unique developmental and functional characteristics, and can contribute to innate immune responses. In addition to their capacity to mount a local antibody response a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(77 citation statements)
references
References 76 publications
3
72
0
2
Order By: Relevance
“…Our LN data during early chronic phase, wk8 post-infection, showed a similar decrease, which persisted in splenic MZ B cells in late chronic phase. This overall decline might be attributable to differentiation of these cells into antibody secreting cells which lose the CD21 hi phenotype as described by Zouali and Richard (Zouali and Richard, 2011). We confirmed in preliminary experiments using ex-vivo TLR ligand stimulation of rhesus macaque splenic B cells that CD21 hi cells are lost 3 days post-stimulation (unpublished).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our LN data during early chronic phase, wk8 post-infection, showed a similar decrease, which persisted in splenic MZ B cells in late chronic phase. This overall decline might be attributable to differentiation of these cells into antibody secreting cells which lose the CD21 hi phenotype as described by Zouali and Richard (Zouali and Richard, 2011). We confirmed in preliminary experiments using ex-vivo TLR ligand stimulation of rhesus macaque splenic B cells that CD21 hi cells are lost 3 days post-stimulation (unpublished).…”
Section: Discussionmentioning
confidence: 76%
“…Colombo et al (2013) reported human splenic MZ B-cells to be CD38 − while Benitez et al (2014) by gating on CD24 and CD38 identified a B-cell population in human spleen characteristic of MZ B-cells that was CD38 + CD21 hi . MZ B-cells play a role in the early immune response to pathogens in a T-independent and T-dependent fashion (Zouali and Richard, 2011). CD38 has been shown to be important for the innate response to Listeria infection (Lischke et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Still, the rise in the proportion of activated memory and marginal-zone B cells in all RhMs, but not AGMs, during chronic SIV infection could contribute to the elevated systemic IgG levels observed during pathogenic infection. Activated memory B cells are induced in response to ongoing viral replication and eventually undergo differentiation into Ig-secreting plasmablasts (45), and marginal-zone B cells play a role in priming T cell-dependent IgG production in response to infection (64). Therefore, it is conceivable that these B cell subsets are partially responsible for the hypergammaglobulinemia observed during chronic SIV infection in RhMs.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, marginal zone B cells act as gatekeepers of innate immunity that modulate maturation and function of innate immune cells, including dendritic cells (DCs), resulting in profound immune suppression. Communication between these "innate-like" B cells and DCs is at least in part facilitated via secretion of IL-10 and CD40-CD40 ligand (CD40L) interaction (73,74). Although both follicular and marginal zone B cells are capable of producing substantial amounts of IL-10, innate-like B cells are able to produce IL-10 independent of B-cell receptor-mediated stimulation but as the result of innate immune activation (75).…”
Section: Discussionmentioning
confidence: 99%